THE INFLUENCE OF VEE DIAGRAM IN THE PROBLEM BASED LEARNING MODEL ON THE BIOLOGY LEARNING COMPETENCE OF SEVENTH GRADE STUDENTS AT SMPN 1 BUNGURAN TIMUR ON THE TOPIC OF POLLUTION AND ENVIRONMENTAL DAMAG - Agustia, Erine -; Syahrial, Eri (BioCONCETTA, 2024)
This research was conducted due to the students’ low learning competence in biology in class VII of SMPN 1 Bunguran Timur. The problem was caused by the students who were passive, had less curiosity, and were unable to correlate between theory and practice, and the limited learning sources available to direct the students to solve problems. On of the ways used to cope with this problem was by applying vee diagram in Problem Based Learning (PBL) model. The purpose of this research was to reveal whether the biology learning competence of the students taught by using vee diagram in PBL model was higher than that of students taught by using PBL model. The quasi-experimental with Randomized Control Group Posttest Only Design and Factorial 2x2 is used in the research. The research were all of the students of class VII of SMPN 1 Bunguran Timur enrolled in the 2023/2024 Academic Year. The sample are taken y purposive sampling technique, VII8 class as an experimental class and VII6 class as an control class. Cognitive instrument using tested objective test as many as 35 items, while affective and psycjomotor instruments using observation sheet. The result showed that the implementation that the implementation of vee diagram in PBL on the pollution and environmental damage topics was more higher than that of students taught by using PBL model, whereas both of them (students with high and low early ability) had higher cognitive competence, and there is no interaction between learning model with early ability toward student learning competence.